Microbial-Derived Polyhydroxyalkanoate-Based Scaffolds for Bone Tissue Engineering: Biosynthesis, Properties, and Perspectives - Li, Jian; Zhang, Xu; Udduttula, Anjaneyulu; Fan, Zhi Shan; Chen, Jian Hai; Sun, Antonia RuJia; Zhang, Peng (Frontiers in Bioengineering and Biotechnology, 2021)
Polyhydroxyalkanoates (PHAs) are a class of structurally diverse natural polyesters, synthesized by a variety of microbes as intracellular carbon and energy storage compounds in response to unbalanced culture conditions. PHAs as biomedical materials have been fabricated in various forms to apply to tissue engineering for the past many years due to their excellent biodegradability, inherent biocompatibility, modifiable mechanical properties, and thermo-processability. However, there remain some bottlenecks in terms of PHA production on a large scale, purity, mechanical properties and biodegradability that need to be further addressed. Therefore, scientists are dint of great efforts via synthetic biology and metabolic engineering tools for improving the properties and the product yields of PHA with the lower cost for the development of various PHA-based scaffolds fabrication technology to widen biomedical applications, especially in bone tissue engineering. This review aims to outline the biosynthesis, structures, properties and the bone tissue engineering applications of PHA scaffolds with different manufacturing technologies. The latest advances will provide an insight into the future outlooks in PHA-based scaffolds for bone tissue engineering.